Strategi Dedolarisasi BRICS dalam Merespon Hegemoni Dolar AS di Pasar Keuangan Global - Wulan Margharetha Rema Saputri (Kajian Ekonomi dan Akuntansi Terapan, 2025)
The US dollar has been the main global currency for quite a long time, which has made other countries dependent on the US economy, and has also become a risk for developing countries and global trading partners. In this situation, the BRICS member countries (Brazil, Russia, Cina and South Africa), planned a dedollarization strategy to create a fair international financial system. This studywill examine the strategy by looking at the monetary, technological and geopolitical aspects, and its impact on developing countries such as Indonesia. Using qualitative methods, especially literature studies, the researcher found that although various efforts have been made such as strengthening local currencies and creating inter-country payment systems,the dominance of the dollar countries. The main challenges include the lack of monetary policy alignment, the low level of financial integration between BRICS members and the impact of geopolitical tensions. These implications show that dedolarization is a process that requires a long time, cooperation, economic stability and technological innovation to become a real alternative to be the dominance of the US dollar in the future.